Invasive Notfalltechniken - INTECH Advanced: REBOA, Perikardiozentese und Clamshell-Thorakotomie - Schneider, Niko; Küßner, Tobias; Weilbacher, Frank; Göring, Martin; Mohr, Stefan; Rudolph, Marcus; Popp, Erik (Notfall & Rettungsmedizin, 2019)
Invasive emergency techniques can be a life-saving factor in specific critical situations but because they are rarely utilized, emergency service and hospital personnel lack experience in performing these procedures. It is therefore required to train medical staff in practice-oriented educational courses in order to be able to adequately apply them in life-threatening situations. The Heidelberg course concept INTECH Advanced focuses on the invasive emergency techniques resuscitative endovascular balloon occlusion of the aorta (REBOA), ultrasound-guided pericardiocentesis and clamshell thoracotomy, which were recently introduced into national and international guidelines. In REBOA a balloon catheter is inserted via the femoral artery and inflated in the descending aorta. In doing so the proximal aortic pressure is increased, which results in a better supply for the heart, lungs and brain. In addition, more distally located bleeding can be reduced or even stopped. The primary function of ultrasound-guided pericardiocentesis is the relief of hemodynamically relevant serous pericardial tamponade in order to stabilize the patient and to bridge the time until definitive operative treatment; however, traumatic hemorrhagic pericardial tamponades are the domain of emergency thoracotomy. In this case the clamshell thoracotomy represents a technique that can be easily learnt, provides a good overview and enables a variety of interventions. The main goal is to relieve a hemorrhagic pericardial tamponade and manual compression of the aorta with the abovementioned effects.
First Online: 26 June 2018
Gesehen am 31.05.2019